Relationship between Knowledge Level about Drug-Resistant TB (TB-RO) and Medication Compliance in Pulmonary TB Patients - Pomalango, Zulkifli B; Arsad, Sitti Fatimah Meylandri; Yusuf, Nur Ayun R.; Antu, Mihrawaty S (Jambura Nursing Journal, 2024)
Introduction: Drug-resistant tuberculosis (TB RO) is still a threat in TB control and is one of the main public health problems in many countries in the world. Globally in 2019, it is estimated that 3.3% of new TB patients and 17.7% of previously treated TB patients will be drug-resistant TB patients. Objective: To determine the relationship between the level of knowledge about Drug-Resistant TB (TB-RO) and the level of medication adherence in pulmonary TB patients. Method: This type of research is quantitative research with analytical observational methods using a cross sectional approach. The population in this study was TB sufferers who were undergoing treatment at the Limboto Community Health Center, totaling 70 respondents. The research technique used accidental sampling to obtain a sample of 35 respondents. Data analysis used the Fishers exact test with the knowledge level questionnaire instrument and MMS-8. Results: The results showed that 29 respondents had good knowledge and were compliant with taking medication, 4 respondents had poor knowledge and were compliant with taking medication, and 2 respondents had poor knowledge and were not compliant with taking medication. The statistical test results showed that p-Value = 0.025, which means less than (Î± = 0.05), indicating that there is a relationship between the level of knowledge about TB-RO and adherence to taking medication. Conclusion: The patient's lack of knowledge about the disease and the use of drugs for therapy results in the patient's lack of understanding of the therapy being undertaken, which causes patient non-compliance in using the medication.